Explanatory model of post-traumatic growth based on anxiety, emotion-focused coping strategies, and irrational ideas in patients with preeclampsia and hypertensive disorders at the National Maternal and Perinatal Institute - Silva Dominguez, Daniel Sergio (2024)
Introduction: Hypertensive disorders during pregnancy affect both the physical and psychological health of patients, potentially influencing their post-traumatic growth. Objective: To evaluate an explanatory model that relates post-traumatic growth to anxiety, emotion-focused coping strategies, and irrational beliefs in patients with preeclampsia and hypertension. Methods: A cross sectional, explanatory correlational study conducted with 351 women treated at the National Maternal Perinatal Institute in 2023. The Post-Traumatic Growth Scale, Generalized Anxiety Disorder Scale (GAD-7), Brief Irrational Beliefs Questionnaire, and Reduced Coping Strategies Inventory (CSI-COPE) were applied. A structural equation model was used to analyze the relationship between variables. Results: The mean age was 30.01 years. The best-fitting model (Chi²=347.043; DF=292; p<0.015; CFI=0.961; TLI=0.957; SRMR=0.055; RMSEA=0.023) indicates that post-traumatic growth is negatively affected by emotional avoidance (E=-0.281; p<0.005), with anxiety (E=0.289; p<0.005) and irrational beliefs (E=0.342; p<0.005) as predictors. Conclusion: An inverse relationship was found between emotional avoidance, anxiety, and irrational beliefs with post-traumatic growth in patients with preeclampsia and hypertension. These findings highlight the need for psychological strategies to improve adaptation and emotional well-being in these patients.